Wing feather mites (Acari: Astigmata) on some passeriformes (aves) from state of paraná, Brazil - Daud, Rodrigo Damasco; Hernandes, Fabio Akashi [UNESP]; Bispo, Arthur Ângelo (Springer Nature, 2015)
Feather mites are the most abundant arthropods found on birds, however, few studies have investigated their ecological associations with their hosts in Brazil. Here, we present a checklist of feather mites on 11 bird species from forest patches of Paraná State, Brazil. We recovered 16 species of feather mites belonging to two astigmatan families, namely Proctophyllodidae and Trouessartiidae. No visible external injuries were observed in the birds which could be related to the presence of these mites on their feathers. We report for first time five feather mite species from Paraná State. The present checklist expands the geographical range for five mite species, with one recorded for the first time in Brazil. Moreover, we have collected two potential new species of the genera Amerodectes and Trouessartia and recorded new bird hosts for three mite species.